2004
DOI: 10.1029/2003gl019122
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of coastal water temperature and microbial pollution at interannual to tidal periods

Abstract: [1] Water temperature and fecal indicator bacteria levels covary along the shoreline of Huntington and Newport Beach, California at interannual to tidal periods. During summer, cooler than average waters caused by interannual variability in sea surface temperature (SST), synoptic upwelling, and tidal-period cooling are coincident with elevated levels of microbial pollution in the surf zone. This relationship can be explained by the effects of weakening in stratification on the fate of a waste water plume and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…Assuming that the positive correlations in 2006 are indicative of cross-shore transport of FIB, these results provide one possible explanation for previous reports of a negative relationship between FIB and nearshore water temperature (Boehm et al, 2004a). Shoreline FIB concentrations were lower in 2005 than in 2006 (Santoro and Boehm, 2007); it is possible that low levels precluded identification of relationships between variables.…”
Section: Discussionmentioning
confidence: 35%
See 2 more Smart Citations
“…Assuming that the positive correlations in 2006 are indicative of cross-shore transport of FIB, these results provide one possible explanation for previous reports of a negative relationship between FIB and nearshore water temperature (Boehm et al, 2004a). Shoreline FIB concentrations were lower in 2005 than in 2006 (Santoro and Boehm, 2007); it is possible that low levels precluded identification of relationships between variables.…”
Section: Discussionmentioning
confidence: 35%
“…The 3-day low-passed near bottom temperature at A and HP (T) showed several long-period cooling events in 10-20 m deep water that lasted for multiple days to weeks (Figs. 4a,5a (Hamilton et al, 2006) and remotely forced nearshore upwelling (Pringle and Riser, 2003;Boehm et al, 2004a), this study does not attempt to examine the observed low-frequency temperature variation and concentrates on the temperature variation and transport at frequencies higher than tidal periods. An expanded view of temperature at A in August 2005 shows that on shorter time scales, the temperature at A was characterized by fluctuations at semi-diurnal and higher frequencies (Fig.…”
Section: Temperature Structurementioning
confidence: 99%
See 1 more Smart Citation
“…We included lagged time series of rainfall and storm runoff as well, because CA beach managers advise beachgoers that beach water quality is impaired by stormwater runoff for 3 days after a storm event. These factors were chosen for inclusion in our study because previous work showed that they can affect FIB densities at beaches (14,(24)(25)(26). Our SI contains information on the data and their sources.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the concentrations of coliforms and heterotrophic bacteria, as well as the prokaryotic secondary production, were highest during the summer months, a season associated with touristic activities increasing local population. Coliforms were also present in the other samples, showing the role of global-scale actions on local-scale pollution, represented by basin scale oscillations, as well as oceanographic and atmospheric processes (Boehm et al 2004). For instance, the role of topography in water circulation explained the presence of fecal indicator bacteria at seaward stations of Senegal coastal waters (Bouvy et al 2008).…”
Section: Anthropogenic Pressurementioning
confidence: 90%